Selection Of High Photosynthetic Productivity Of Broad Bean (Vicia Faba L.) Lines (Diversity Research: Journal of Analysis and Trends, 2023)
Bean (Vicia faba L.) is one of the legumes that has the potential to be grown as a multi-purpose crop in areas with a short growing season. Bean (Vicia faba L.) is cultivated in many regions of the world due to its high nutritional value, medicinal properties and efficient biological fixation of nitrogen. In this paper, the photosynthetic productivity indicators of bean (Vicia faba L.) cultivars and ridges during branching and podding are analyzed. According to the results of the research, with the formation of pods of the bean crop, the plant's water demand increased, when the total water content of the plant was analyzed, it was found that it was low in 9 ridges, and these ridges transferred 27.7-57.4 percent of the evaporated water to transpiration, and the remaining 42.6-72 it was found that 3 percent is used for the formation of organic matter